Innovation and multi-actor cross-border cooperation in central Pyrenees to improve sustainability of local sheep breeds: PIRINNOVI project - Lahoz B.; Jousseins C.; Calvo J.H.; Papuchon J.; Alabart J.L.; Pardos L.; Loywyck V.; Serrano M.; Soulas C.; Eguinoa P.; Tortereau F.; Fantova E.; et al. (Innovation for sustainability in sheep and goats, 2019)
Sheep farming of local breeds in the Pyrenean region is of major significance from an economic, social and environmental viewpoint. However, this activity is in continuous recession. Common problems are found in both sides of the border, in France and in Spain: its scarce profitability and a lack of generational renewal, due in part to the lack of innovation linked to its particular geographic isolation. The PIRINNOVI project aims at establishing a network for acquisition, exchange and transfer of field knowledge but also research methodologies to improve sheep farming sustainability by the way of management and reproductive genetics. Common indicators for sustainability are being designed to perform technical-economic, social and environmental studies. Regardless of breed, increasing efficiency is a key factor to improve sustainability of sheep production. Thus, PIRINNOVI focuses on common reproductive problems like the low efficiency of selection schemes for prolificacy and maternal effects on growing lambs. For this purpose, artificial insemination protocol review, automatization of lamb weight recording, next-generation sequencing (NGS) and other genomic technologies based on SNP arrays are being used in both countries. The opinion of farmers, technicians and other users of the Pyrenean territory on these innovations and their implications for the continuity of this activity are also studied and taken into account for the future.
2. Joint Seminar of the Subnetworks on Nutrition and on Production Systems of the FAO-CIHEAM Network for Research and Development in Sheep and Goats, 2017/10/03-05, Vitoria-Gasteiz (Spain)